PELATIHAN PEMBELAJARAN BERBASIS DIGITAL DALAM IMPLEMENTASI MERDEKA BELAJAR DAN BELAJAR DI RUMAH BAGI GURU-GURU MGMP PPKn SE-KOTA TERNATE - Hasyim, Rustam; Kamisi, Mohtar (Universitas Khairun, 2021)
This Community Service (PKM) is carried out on the basis of an analysis carried out by exploring the needs of teachers in the Citizenship Education MGMP (PPKn) of Ternate City. The results of the confirmation of some of the most relevant teacher needs to be addressed are the problem of the ability and skill needs to compose digital/online-based learning materials, because they are related to the application of learning from home. This is because the community is currently facing an outbreak of the COVID-19 Pandemic which has resulted in learning at school being replaced by learning from home. The problem of digital-based learning is important to be used as material in this PKM activity because it accommodates the needs of teachers in PBM who are currently faced with the necessity of learning activities from home as a result of the pandemic outbreak. The strategy for delivering the material is taken through: WA Group/internet/online, Face-to-face if the COVID-19 outbreak conditions have subsided and the situation allows for face-to-face meetings. The form of activities and strategies/problem solving methods that will be carried out is training related to the effectiveness of digital-based learning by implementing the following activity steps: (1) Determining the location to be targeted for the training, namely MGMP Citizenship Education (PPKn) teachers in Ternate City with a total number of involved 20 teachers. (2). Provide training materials through online and or face-to-face (according to conditions) which include: Digital-based learning concepts, and tracking digital-based historical materials (Journals, E-Books, Student Books, Google, etc.). Converts non-digital data (text/book data, natural data, Image Data, Sound Data, etc.) into digital data (WORD/Docx, Ecxel/xlsx, JPG, Image, PDF, PPT files, etc.) convert (Convert) digital data as needed (Word to PDF, PDF to Word, JPG to PDF, etc.). (3). Compiling historical materials/materials for Elearning/Vlearning (4).Using various learning video call facilities (face to face) through Teleconference facilities (WA video call, Zoom, Google Schooler, Vlearn, etc.). The output target of this PKM is that teachers who are members of the MGMP who take part in the training as participants have the understanding and skills related to digital-based history learning so that they can support learning from home and the implementation of independent learning.